ESTRATÉGIAS DE DISTRIBUIÇÃO E COMERCIALIZAÇÃO DE UMA EDITORA UNIVERSITÁRIA DO RIO GRANDE DO SUL - VIEIRA, EUSÉLIA P.; SANTOS, INAJARA C. D.; SCHNEIDER, VANDERLEI E. (Salão do Conhecimento, 2013)
Resumo